Serum non‐coding RNAs for diagnosis and stage of liver fibrosis. Issue 10 (21st August 2022) - Liu, Chao; Hou, Xueyun; Mo, Kaixin; Li, Nannan; An, Cheng; Liu, Guijian; Pan, Zongdai
Abstract: Background: All chronic liver diseases could lead to liver fibrosis. Accurate diagnosis and stage of fibrosis were important for the medical determination, management, and therapy. Liver biopsy was considered to be the gold criteria of fibrosis diagnosis. However, liver biopsy was an invasive method with some drawbacks. Non‐invasive tests for liver fibrosis included radiologic method and serum‐based test. Radiologic examination was influenced by obesity, cost, and availability. Serum‐based test was widely used in the screening and diagnostic of liver fibrosis. However, the accuracy was still needed to be improved. Methods: Recent studies showed serum non‐coding RNAs: microRNA, long non‐coding RNA(lncRNA), and circular RNA(circRNA), which have the potentiality to be non‐invasive markers for liver fibrosis. The recent progress was summarized in this review. Results: These studies showed serum non‐coding RNAs exerted a good diagnostic performance for liver fibrosis. A panel that included several non‐coding RNAs could increase the accuracy of single marker. Conclusions: Serum microRNAs, lncRNAs, and circRNAs could be potential non‐invasive markers for diagnosis and stage of liver fibrosis. More high‐quality clinical study is needed for further research. Abstract : MicroRNAs, lncRNAs, circRNAs and exosomes which were released from liver enter into circulating vessels. The blood which contain these molecules are drawed from patients. Then the blood specimen are tested for diagnose of early fibrosis or stage fibrosis in patients with liver diseases.